Analysis of Multi-Cell Production Systems Considering Cell Size and Worker Flexibility - Ruiz-Torres, Alex J; Mahmoodi, Farzad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This simulation study investigates the performance of a number of multi-cell configurations generated by altering the cell size, worker flexibility and shop type, under a variety of experimental conditions. The experimental factors considered are product mix balance, due date tightness, and setup-to-processing-time ratio. The study is motivated by the challenges faced by an electronic manufacturer to design an efficient and effective multi-cell production system. The results demonstrate that everything else being equal, small cells perform better under low setup times and loose-to-moderate due date tightness levels, while larger cells perform better under high setup times and tight due date environments. Furthermore, the performance of larger cells is more robust with respect to due date tightness factor than that of smaller cells. It is also shown that the presence of some routing flexibility in the shop significantly enhances the performance of the small cells. However, shops with no routing flexibility need to be large to perform effectively, especially when facing constraints such as tight due dates and extreme product mix unbalance.